Article Review: Identifications and Geographic Distribution of Six Anisakis Species (Nematoda: Anisakidae) in Indonesia - Indaryanto, Forcep Rio; Kamal, Mohammad Mukhlis; Butet, Nurlisa A.; Affandi, Ridwan; Tiuria, Risa (Jurnal Veteriner, 2024)
Anisakis is a zoonotic nematode that causes anisakiasis in Europe and Asia. Food safety has recently become a major concern for consumers; therefore, accurate identification of Anisakis larvae is necessary for the correct diagnosis of Anisakis infection in humans and fish and for improving food safety. From 2001 to 2023, Anisakis examinations were carried out in 33 areas of Indonesian territory. Morphometric Anisakis of Indonesia generally have a body length of 0.10-34.50 mm with a diameter of 0.30-0.42 mm. Based on morphological and genetic identification, identified six species anisakis in Indonesia ( A. simplex, A. physeteris, A. pegreffii, A. berlandi, A. typica and Anisakis sp. HC-2005 ), or identified six Anisakis genotypes based on genetic identification, namely A. typica (s.s), A. typica var Indonesiansis, A. physeteris, A. pegreffii, A. berlandi and Anisakis sp . HC-2005. Decapterus sp., Thyrsitoides marleyi, Euthynnus afifinis, Auxis rochei, Gempylus serpens , Katsuwonus pelamis and Trichiurus lepturus have a high prevalence (>90%), indicating that they are often infected with Anisakis. Anisakis spread throughout the waters in Indonesia with various types of fish as hosts and A. typica is the predominant species in Indonesia.